In vitro and in vivo activity of novel platinum(ii) complexes with naphthalene imide derivatives inhibiting human non-small cell lung cancer cells. (13th May 2019) - Huang, Guo-Bao; Chen, Shan; Qin, Qi-Pin; Luo, Jin-Rong; Tan, Ming-Xiong; Wang, Zhen-Feng; Zou, Bi-Qun; Liang, Hong
Abstract : 3 induced NCI-H460 cell apoptosis via inhibition of the telomerase and dysfunction of mitochondria. Remarkably, 3 obviously inhibited NCI-H460 xenograft tumor growth in vivo. Abstract : Four new Pt(ii ) complexes, [Pt(L a )]Cl (1 ), [Pt(L b )]Cl (2 ), [Pt(L c )]Cl (3 ) and [Pt(L d )]Cl (4 ) with the naphthalene imide derivatives L a –L d as ligands were designed and prepared. MTT assay indicated that1–4 exhibited proliferation inhibiting activity against human non-small cell lung cancer (NCI-H460) cells, especially1–3 showed superior activity (IC50 = 0.10–8.56 μM) compared with cisplatin (IC50 = 12.01 ± 1.03 μM). Various experiments showed that3 as a telomerase inhibitor induced NCI-H460 cell apoptosis via inhibition of the telomerase and dysfunction of mitochondria. In vivo evaluation results suggested that3 could significantly inhibit the growth of tumor cells in NCI-H460 tumor-bearing mice and the tumor growth inhibition rate (TGI) reached 40.7%. These results demonstrated that3 is a telomerase inhibitor and a promising anti-cancer agent.